Penerbitan Sertifikat Hak Atas Laut dalam Perspektif Hukum Agraria dan Hukum Laut Internasional - Manalu, Karto (IAI Nasional Laa Roiba Bogor, 2025)
The issuance of certificates of sea rights is a complex legal issue because it involves aspects of agrarian law and international maritime law. In the context of agrarian law in Indonesia, the recognition of rights to sea areas does not yet have an explicit legal basis like land rights. Meanwhile, international maritime law, especially through the 1982 UN Convention on the Law of the Sea (UNCLOS), regulates state jurisdiction over waters, including the exclusive economic zone and continental shelf, but does not specifically discuss private ownership of the sea. This study uses a qualitative method with a juridical-normative approach to analyze the unclear regulations regarding sea rights in Indonesia and how international legal principles can provide direction for their development. The results of the study show that the disharmony between national law and international law creates legal uncertainty for individuals or entities claiming sea rights. In addition, the policy of issuing sea rights certificates requires a clearer legal framework so as not to conflict with the principles of sustainable marine resource management. Therefore, policy recommendations are needed to align national regulations with international standards to ensure legal certainty and protection of public interests and the marine environment.